Correlations of HBV Genotypes, Mutations Affecting HBeAg Expression and HBeAg/ anti-HBe Status in HBV Carriers - Lim, Chee Kent (Ivyspring International Publisher, 2006)
This study was carried out to determine the effects of hepatitis B virus genotypes, core promoter mutations (A1762G1764→T1762A1764) as well as precore stop codon mutations (TGG→TAG) on HBeAg expression and HBeAg/ anti-HBe status. Study was also performed on the effects of codon 15 variants (C1858/ T1858) on the predisposition of precore stop codon mutations (TGG→TAG). A total of 77 sera samples were analyzed. Fifty one samples were successfully genotyped of which the predominant genotype was genotype B (29/ 51, 56.9 %), followed by genotype C (16/ 51, 31.4 %). Co-infections by genotypes B and C were observed in four samples (7.8 %). To a lesser degree, genotypes D and E (2.0 % each) were also observed. For core promoter mutations, the prevalence was 68.8 % (53/ 77) for A1762G1764 wild-type and 14.3 % (11/ 77) for T1762A1764 mutant while 9.1 % (7/ 77) was co-infected by both strains. The prevalence of codon 15 variants was found to be 42.9 % (33/ 77) for T1858 variant and 16.9 % (13/ 77) for C1858 variant. No TAG mutation was found. In our study, no associations were found between genotypes (B and C) and core promoter mutations as well as codon 15 variants. Also no correlation was observed between HBeAg/ anti-HBe status with genotypes (B and C) and core promoter mutations.